Effectiveness of a 30‐year periodontist's primary care for 1946 patients during five‐year follow‐up. (17th March 2021) - Lai, Hongmin; Yen, Amy Ming‐Fang; Chen, Sam Li‐Sheng; Chen, Tony Hsiu‐Hsi
Abstract: Objective: To evaluate the effect of the periodontal primary care (PPC) on the improvement of periodontal probing depth based on a periodontist's 30‐year practice. Materials and Methods: We enrolled a total of 2, 894 patients who underwent periodontal basic treatment between 1987 and 2017 with 84.5% retention rate. The study population was composed of 80% ( n  = 1, 946) of retained patients with complete re‐evaluation up to five‐year follow‐up. The outcome was measured by the improvement of probing depths (graded as 1:1–3 mm; 2:4–6 mm; 3: ≥7 mm) before and after PPC on both sextant and patient levels. Whether a better improvement was seen in the surgical group and the non‐smoker group opposed to their comparators was assessed with various multi‐variable regression models. Results: On patient (sextant) level, 82% (38%) improved, 13% (59%) unchanged, and 5% (3%) deteriorated. Adjusted better improvement of probing depth was noted for the surgical group by 63% and non‐smoker by 31% compared with their counterparts. The similar findings were found for the outcomes based on continuous probing depth scores. Conclusions: We demonstrate the improvement of probing depth scores with a periodontal primary care offered for the retained patients and larger effect for the surgical group and non‐smoker patients.